Project feasibility study on Mapa ng Loob an online Filipino personality test - Collado, Angelo Immanuel G.; Del Rosario, Francisco Luis A.; Ednalino, Kenneth Anthony G.; Macabanti, Jerome A.
The purpose of this study is to evaluate the feasibility of Masaklaw na Panukat ng Loob (Mapa ng Loob, or Mapa) - a personality-testing instrument, developed by Dr. Gregorio E. H. del Pilar and his team from the University of the Philippines, Diliman. Mapa utilizes the "Five-Factor Model" (a famously established personality framework) as its foundation, but appropriates this model to best suit the cultural norms of Filipinos. As a product-cum-service to be distributed and sold, Mapa consists of both a questionnaire to be filled up by the test-taker's, and the subsequent evaluation of the test-taker's results to assess his or her personality. With regards to its demand in the market, it was found that Mapa would find most success in both the service and the manufacturing industry. Its ideal end-users (test- takers) would be newly-recruited job applicants and high-level executives. With this, it was found that the most effective way to reach the target audience would be through third-party Human Resource organizations. These organizations who normally administer personality tests to various companies will serve as Mapa's intermediate clients. The reliability of Mapa - particularly, the scientific research that went into its creation as well as its cultural relevance to Filipinos - gives it a competitive edge against other personality testing instruments in the market. Based on pricing analysis, the most favorable price that one would have to pay to gain access to the test questionnaire is Php 200. Based on forecasted figures (derived from national statistics regarding job referrals, sector growth, and employment rates), the expected five-year demand, and revenue from questionnaire access are as follows: In order to attain these numbers for the predicted demand, Mapa will have to center its marketing promotions around education of the public with regards to the proper use of personality testing instruments in the industry. It was found that an online administration of the test would be most suitable for the target market. This includes the purchase of an online Administrator's Account for Php 1000 in order to distribute access to test, and viewing of automatically generated test results. Mapa will also offer an on-site computer room facility where test-takers can answer the test. Both this facility, and the office of Mapa will be based in Makati due to its proximity to the clients. In order to operate properly, Mapa will need to employ computer programmers, marketing staff, and a licensed psychometrician. Below is a category-based breakdown of the total aggregated costs for Mapa over the next 5 years. The project was shown to be financially feasible with a positive Net Present Value of Php 87,464,110.38 and an Internal Rate of Returns at 183.55%, which is much greater than the Minimum Acceptable Rate of Return, or the opportunity cost at which investors will incur when they put their money in other current investments. Another indicator of Mapa being a good investment is that its profitability ratios show very good numbers, wherein the Return on Equity and Return on Assets have been consistently higher than the industry's ROE and ROA for each year of the 5-year period. By the end of its 5th year of operation, it was predicted that Return on Equity would be at 31.39%, Return on Assets would be at 22.01%, and its Net Profit Margin would be at 41.63%, the largest during that period. Payback period would take approximately 1 year. In order to finance the project, a capital fund of Php 2,000,000.00 will be acquired by issuing a total of 10.000 shares with a par value of Php 200.00. As for the socio-economic feasibility of Mapa, the study used the cost-benefit analysis to discuss the various social effects of implementing the project. It was seen that savings from foreign exchange of importing psychological tests, promotion of local psychological testing instruments, and better job fit for Filipino applicants and employees are the main benefits, while environmental footprint caused by consumption of electricity and water, as well as the waste the company produce contribute to the costs of Mapa. With each year's BC ratio being greater than 1 and the net present BC ratio of the project projected to be at 26:56, it can be concluded that the project is socially profitable and feasible. With further research being done on the test, Mapa can definitely improve the productivity and performance of workers, employees and executives through proper job-fit. As it stands, Mapa is feasible in every way, and is ready to be launched in the market.